Penerapan Terapi Relaksasi Otogenik Untuk Meningkatkan Kualitas Tidur Lansia Hipertensi Dengan Masalah Gangguan Pola Tidur - Nova Natalia Beba; Juliana Neng Rifka Sarman; Elkid Elkid (Yayasan Ekselensi Daya Indonesia, 2025)
Hypertension is an increase in blood pressure that can cause sleep disorders. Sleep pattern disorders are where individuals experience sleep disorders including difficulty falling asleep, waking up in the middle of the night, and waking up too early. Autogenic relaxation is a relaxation that comes from positive suggestions that have been proven to have a calming effect on individuals and can improve sleep quality. This relaxation is easy to do, does not require cost, and does not require training. This study aims to describe nursing care with the application of autogenic relaxation techniques to improve sleep quality. The method used in this study is a descriptive case study method. Data collection was carried out through interviews and observations. The instrument used was the PSQI Assessment, with sleep pattern disorders related to lack of sleep control according to the signs and symptoms in the SDKI. The interventions given were 4 interventions following SIKI with the application of autogenic relaxation techniques. Results: After autogenic relaxation therapy was applied for 3 meetings, the PSQI assessment results decreased from 9 to 5, meaning good sleep quality. This study concludes that autogenic relaxation can improve the sleep quality of elderly hypertensive patients. It is hoped that from the results of this special study, respondents will be able to apply autogenic relaxation techniques independently.